AN ANALYSIS PHILOSOPHICAL ON BODY IN MOTION AND PROCESSORS ACTIONS OF NATURE (Fiep Bulletin - online, 2013)
From the criticism of the current form of social organization and economic opportunities can be identified overrun by awareness and education, reorganizing the pedagogical practice in order to form a human being not realized, with itself and with nature, valuing space and time to free action, artistic and creative revolutionary impact of individual and collective, local globais.Este text search and analyze the relationship between humans and their actions transformative in nature, identifying key issue in the disposal process of environmental destruction.
Keywords: nature; human being; behavior; body